Targeted gene panel sequencing in children with very early onset inflammatory bowel disease—evaluation and prospective analysis. Issue 11 (5th September 2014) - Kammermeier, Jochen; Drury, Suzanne; James, Chela T; Dziubak, Robert; Ocaka, Louise; Elawad, Mamoun; Beales, Philip; Lench, Nicholas; Uhlig, Holm H; Bacchelli, Chiara; Shah, Neil
Abstract : Background: Multiple monogenetic conditions with partially overlapping phenotypes can present with inflammatory bowel disease (IBD)-like intestinal inflammation. With novel genotype-specific therapies emerging, establishing a molecular diagnosis is becoming increasingly important. Design: We have introduced targeted next-generation sequencing (NGS) technology as a prospective screening tool in children with very early onset IBD (VEOIBD). We evaluated the coverage of 40 VEOIBD genes in two separate cohorts undergoing targeted gene panel sequencing (TGPS) (n=25) and whole exome sequencing (WES) (n=20). Results: TGPS revealed causative mutations in four genes ( IL10RA, EPCAM, TTC37 and SKIV2L) discovered unexpected phenotypes and directly influenced clinical decision making by supporting as well as avoiding haematopoietic stem cell transplantation. TGPS resulted in significantly higher median coverage when compared with WES, fewer coverage deficiencies and improved variant detection across established VEOIBD genes. Conclusions: Excluding or confirming known VEOIBD genotypes should be considered early in the disease course in all cases of therapy-refractory VEOIBD, as it can have a direct impact on patient management. To combine both described NGS technologies would compensate for the limitations of WES for disease-specific application while offering the opportunity for novel gene discovery in the research setting.